Livelihood diversification of coastal women in Padelegan Village, Pamekasan Regency, Indonesia - Novi DB Tamami; Sri Ratna Triyasari; Fuad Hasan; Meliana Ahdiningtyas; Achmad Kusairi Sam (Agriekonomika, 2024)
Coastal women play a strategic role in sustaining the economic resilience of fishermen’s households, whose income is highly uncertain and dependent on seasonal and weather conditions. This study aims to identify the types of occupations undertaken by coastal women in Padelegan Village, Pademawu District, Pamekasan Regency, and to determine the percentage distribution of these occupations. The research employed a descriptive qualitative method using purposive sampling involving 30 respondents. Data were collected through semi-structured interviews, observation, and documentation.The findings reveal that the majority of coastal women are within the productive age group and have a primary school educational background. The dominant occupation is anchovy processing factory labor (46.7%), followed by fish vendors (33.3%), small-scale fishery-based entrepreneurs (6.7%), and other activities such as cleaning, sorting, and drying fish (each 3.3%). These results indicate that women’s economic participation is concentrated in informal fishery processing and marketing sectors.Such economic involvement reflects a dual role pattern, in which women simultaneously perform domestic responsibilities and productive economic activities to supplement household income. Therefore, coastal women in Padelegan Village demonstrate a substantial contribution as an adaptive strategy of fishermen’s households in coping with economic uncertainty.